2016
DOI: 10.1155/2016/8527849
|View full text |Cite
|
Sign up to set email alerts
|

In VitroEvaluation of Bacterial Leakage at Implant-Abutment Connection: An 11-Degree Morse Taper Compared to a Butt Joint Connection

Abstract: Background and Aim. The geometry of implant-abutment interface (IAI) affects the risk of bacterial leakage and invasion into the internal parts of the implant. The aim of this study was to compare the bacterial leakage of an 11-degree Morse taper IAI with that of a butt joint connection. Materials and Methods. Two implants systems were tested (n = 10 per group): CSM (submerged) and TBR (connect). The deepest inner parts of the implants were inoculated with 2 μL of Streptococcus mutans suspension with a concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
(21 reference statements)
1
12
0
2
Order By: Relevance
“…27 Previous published studies also concluded that the conical connection had better resistance than nonconical ones against both mechanical deformation and bacterial invasion. 15,28,29 These rate between the two types of connection studied here was found clinically. 30 It appears that the size of the micro-gap does not relate to crestal bone loss either.…”
Section: Evaluation Based On Micro-ct Imagessupporting
confidence: 63%
See 3 more Smart Citations
“…27 Previous published studies also concluded that the conical connection had better resistance than nonconical ones against both mechanical deformation and bacterial invasion. 15,28,29 These rate between the two types of connection studied here was found clinically. 30 It appears that the size of the micro-gap does not relate to crestal bone loss either.…”
Section: Evaluation Based On Micro-ct Imagessupporting
confidence: 63%
“…Some researchers measured the concentration of the penetrant, such as absorbance of the dye or bacterial count, to evaluate the volume of leakage. 15,28 However, the concentration of silver nitrate inside the implant was highly dependent on the drying time and the size of gap opening after loading. Using the data from micro-CT to quantify the volume of silver nitrate is possible but isolating the silver nitrate is very sensitive to the choice of the grayvalue threshold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Implants with an internal taper connection and platformswitching can provide better protection against microbial leakage and soft tissue inflammation by reducing the microgap at the implant-abutment interface and increasing the distance to the bone crest, as well as allowing for a greater amount of connective tissue around the implant that functions as a cuff-like barrier (D'Ercole et al, 2014;Khorshidi, Raoofi, Moattari, Bagheri, & Kalantari, 2016;Lazzara & Porter, 2006;Tenenbaum, Schaaf, & Cuisinier, 2003). The subcrestal placement of dental implants may avoid the exposure of implant threads after initial physiologic bone remodeling and allow an adequate esthetic emergence profile for the prosthetic restoration (Koutouzis et al, 2014;Palaska, Tsaousoglou, Vouros, Konstantinidis, & Menexes, 2016;Vervaeke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%